Hard Pitch Lake, La Brea, Trinidad B.W.I. - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, Trinidad, 2009)
Photo of Hard Pitch Lake at La Brea, Trinidad. Some persons visible are digging the hard pitch while others are observing. At top and centre of this postcard one can see a cart waiting to transport the pitch.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Pitch--Trinidad and Tobago; Asphalt industry--Trinidad and Tobago; Working class--Trinidad and Tobago; Cities and towns--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Pitch Lake, The (La Brea)